Cognitive, Motor, and Language Assessment in Children with Human Immunodeficiency Virus - Apsari, Putu Indah Budi; Supadma, I Nyoman; Wati, Ketut Dewi Kumara; Artana, I Wayan Dharma (Folia Medica Indonesiana, 2022)
Highlights: • HIV-infected children had lower capute scores than normal children. • HIV child age range 12-24 months almost suffer delayed speech, and were in suspect criteria was founded. Abstract: The cognitive, motor and language aspect of HIV-infected children is an important issue affecting their quality of life. The capute scale, divided into Cat and Clams scores, is commonly used to assess children's cognitive, motor, and language functions. This study assessed Cat and Clams' scores of HIV-infected children. We performed Cat and Clams assessment on 136 children consisting of 68 HIV-infected children and 68 normal children as control aged 0-36 months. The Capute scale examined both groups at the first meeting (first month), and for the rest six months, we evaluated the progress of cognitive, motor, and language development. In the first meeting, we found that HIV-infected children had significantly low capute scores than the control group. The sixth-month Capute score in HIV-infected children was also significantly lower than the control group. HIV-infected children had lower Capute scores than normal children.